Semantic interoperability : issues, solutions, and challenges - Pileggi, Salvatore F.; Fernandez-Llatas, Carlos (River Publishers series in information science and technology., 2012)
The Semantic Interoperability model would improve common interoperability models introducing the interpretation of means of data. In practice, semantic technologies are partially inverting the common view at actor intelligence: intelligence is not implemented (only) by actors.